Mycobacterium tuberculosis PhoY Proteins Promote Persister Formation by Mediating Pst/SenX3-RegX3 Phosphate Sensing - Sarah B. Namugenyi (American Society for Microbiology, 2017)
ABSTRACT The Mycobacterium tuberculosis phosphate-specific transport (Pst) system controls gene expression in response to phosphate availability by inhibiting the activation of the SenX3-RegX3 two-component system under phosphate-rich conditions, but the mechanism of communication between these systems is unknown. In Escherichia coli, inhibition of the two-component system PhoR-PhoB under phosphate-rich conditions requires both the Pst system and PhoU, a putative adaptor protein. E. coli PhoU is also involved in the formation of persisters, a subpopulation of phenotypically antibiotic-tolerant bacteria. M. tuberculosis encodes two PhoU orthologs, PhoY1 and PhoY2. We generated phoY single- and double-deletion mutants and examined the expression of RegX3-regulated genes by quantitative reverse transcription-PCR (qRT-PCR). Gene expression was increased only in the ΔphoY1 ΔphoY2 double mutant and could be restored to the wild-type level by complementation with either phoY1 or phoY2 or by deletion of regX3. These data suggest that the PhoY proteins function redundantly to inhibit SenX3-RegX3 activation. We analyzed the frequencies of antibiotic-tolerant persister variants in the phoY mutants using several antibiotic combinations. Persister frequency was decreased at least 40-fold in the ΔphoY1 ΔphoY2 mutant compared to the frequency in the wild type, and this phenotype was RegX3 dependent. A ΔpstA1 mutant lacking a Pst system transmembrane component exhibited a similar RegX3-dependent decrease in persister frequency. In aerosol-infected mice, the ΔphoY1 ΔphoY2 and ΔpstA1 mutants were more susceptible to treatment with rifampin but not isoniazid. Our data demonstrate that disrupting phosphate sensing mediated by the PhoY proteins and the Pst system enhances the susceptibility of M. tuberculosis to antibiotics both in vitro and during infection. IMPORTANCE Persister variants, subpopulations of bacteria that are phenotypically antibiotic tolerant, contribute to the lengthy treatment times required to cure Mycobacterium tuberculosis infection, but the molecular mechanisms governing their formation and maintenance are poorly characterized. Here, we demonstrate that a phosphate-sensing signal transduction system, comprising the Pst phosphate transporter, the two-component system SenX3-RegX3, and functionally redundant PhoY proteins that mediate signaling between Pst and SenX3-RegX3, influences persister formation. Activation of RegX3 by deletion of the phoY genes or a Pst system component resulted in decreased persister formation in vitro. Activated RegX3 also limited persister formation during growth under phosphate-limiting conditions. Importantly, increased susceptibility to the front-line drug rifampin was also observed in a mouse infection model. Thus, the M. tuberculosis phosphate-sensing signal transduction system contributes to antibiotic tolerance and is a potential target for the development of novel therapeutics that may shorten the duration of tuberculosis treatment.